2019
DOI: 10.1111/jphs.12292
|View full text |Cite
|
Sign up to set email alerts
|

Developing and piloting a serious game to educate children about over‐the‐counter medication safety

Abstract: Objective Misuse of over‐the‐counter (OTC) medications among children is a growing public health and medication safety problem. Serious games are increasingly being used to foster healthy self‐management behaviours and decision‐making among children. We developed and pilot‐tested using a serious game to educate children about OTC medication safety. Methods Students (aged 15–17) at a public school serving grades 6–12 in Western Pennsylvania were recruited to play the game. Open‐ended questions were asked follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…• Games for antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) adherence: Viral Combat, Adherence Warrior, Epic Allies, and Battle Viro were developed to promote adherence to ART and PrEP [26][27][28][29][30] • Game for cancer treatment medication adherence: Re-Mission [31] • Game for diabetes medication education and adherence: L'Affaire Birmann [32,33] • Game for asthma medication education: Wee Willie Wheezie [34] • Games for microbiology and antibiotic education: Microbe Quest and e-Bug Junior and Senior [35][36][37] • Game for prescription drug abuse education: CSI Web Adventures [38] • Game for over-the-counter (OTC) medication safety: Alchemy Knights [39]…”
Section: Intention Of the Serious Gamementioning
confidence: 99%
“…• Games for antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) adherence: Viral Combat, Adherence Warrior, Epic Allies, and Battle Viro were developed to promote adherence to ART and PrEP [26][27][28][29][30] • Game for cancer treatment medication adherence: Re-Mission [31] • Game for diabetes medication education and adherence: L'Affaire Birmann [32,33] • Game for asthma medication education: Wee Willie Wheezie [34] • Games for microbiology and antibiotic education: Microbe Quest and e-Bug Junior and Senior [35][36][37] • Game for prescription drug abuse education: CSI Web Adventures [38] • Game for over-the-counter (OTC) medication safety: Alchemy Knights [39]…”
Section: Intention Of the Serious Gamementioning
confidence: 99%
“…Teaching medical knowledge through the form of games has been found to be as effective as traditional text-based teaching methods [12]. In addition to teaching accurate information in a guided and context-based manner, incorporating knowledge pertaining to food and drug safety into video games has been proven to effectively raise the level of relevant knowledge among youngsters [13,14]. Moreover, teaching cardiopulmonary resuscitation through serious games has also been shown to result in a higher retention rate of knowledge and skills [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Serious games are computer or video games designed for the primary purpose of educating users beyond entertainment purposes (eg, educational games, exercise video games, language learning games) [19][20][21][22]. Studies have demonstrated that serious games are effective in sharing information as well as changing attitudes and behaviors in a variety of health domains, such as safe sex [23], healthy eating [24][25][26], cancer [27,28], smoking [29,30], exercise [31][32][33], asthma management [34,35], and over-the-counter medication [36].…”
Section: Serious Gamesmentioning
confidence: 99%